2015
DOI: 10.1161/circulationaha.114.013710
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-Mediated Reduction in Proapoptotic Molecule Bim Renders CD4 + CD28 null T Cells Resistant to Apoptosis in Acute Coronary Syndrome

Abstract: 709M yocardial infarction and stroke caused by atherosclerosis are the most frequent cardiovascular causes of death and disability in the world despite the progress in prevention and therapy.1 Recent evidence clearly implicates the innate and adaptive immune system in the pathogenesis of atherosclerosis.2 T lymphocytes, the main orchestrators of adaptive immune responses, have pivotal roles in atherosclerosis. In particular, proinflammatory CD4+ T lymphocytes such as T helper 1 cells have been shown to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 42 publications
4
40
0
2
Order By: Relevance
“…These cells express multiple cytotoxins including granzymes A and B, perforin and granulysin as well as pro‐inflammatory cytokines IFN‐γ and TNF‐α (Teo et al, ). They are highly resistant to apoptosis (Kovalcsik et al, ) and appear to accumulate in vulnerable coronary atherosclerotic plaques (Nakajima et al, ). Activation appears to be triggered by heat shock protein 60 antigens (Zal et al, ; Zal et al, ) and by the co‐stimulatory molecules Ox40 (CD134) and 41BB (CD137) present on CD4 + CD28−T cells in acute coronary syndromes (Dumitriu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These cells express multiple cytotoxins including granzymes A and B, perforin and granulysin as well as pro‐inflammatory cytokines IFN‐γ and TNF‐α (Teo et al, ). They are highly resistant to apoptosis (Kovalcsik et al, ) and appear to accumulate in vulnerable coronary atherosclerotic plaques (Nakajima et al, ). Activation appears to be triggered by heat shock protein 60 antigens (Zal et al, ; Zal et al, ) and by the co‐stimulatory molecules Ox40 (CD134) and 41BB (CD137) present on CD4 + CD28−T cells in acute coronary syndromes (Dumitriu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CD41CD28 null T cells are less sensitive to glucocorticoid-mediated suppression (19). Such reduced sensitivity to glucocorticoids could be due to expression of antiapoptotic molecules (20,21), alternative signaling pathways and costimulatory receptors (22,23), and/or lower expression of glucocorticoid receptors (24). The potential contribution of CD28 null T cells to muscle damage in polymyositis is still unknown, although we have previously demonstrated that the infiltrating T cells in affected muscle of polymyositis patients are predominantly CD81CD28 null and CD41CD28 null T cells (7).…”
mentioning
confidence: 99%
“…A growing body of evidence has implicated UPS in neointimal formation . Recent studies have identified increased activity of ubiquitination–proteasome in neointimal areas and furthermore, inhibition of UPS by MG132 effectively reduced neointima formation in vivo, which corresponds to strong antiproliferative effects in vitro and in vivo, suggesting the UPS as a new target in the prevention of vascular restenosis . However, the specific protein targets of UPS remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%